«La (per così dire) energia delle figure» - Bertrand Rougé (Aisthesis, 2012)
What is it that makes an artwork function and present itself as an artwork distinct from non-art? Such is the question of the artwork’s persuasive evidence. Through a re-reading of the rhetorical literature about ekphrasis — enargeia that grounds it and energeia that motivates it — this paper attempts to describe the artwork in its dynamic dimension, as an occasion to move (phora and transitus). The stress is then put on the energetic movement of the «pro ommaton poiein» which is specific of how a figure functions, but it is then demonstrated that this is the movement of the figure per se, dissociable from classic mimesis and its «cinematographical fantasy». A few examples are then analyzed to show how this global theory may encompass trompe-l’œil as well as plasticity, redaymades or abstract art, thus launching a possible «energetics of art».